A Production and operations management study of Saldana & Company, Incorporated. - Cariño, Don Mikhail; Granados, Geronimo; Zafico, Mikhail (Diliman, Quezon City College of Engineering, 1997)
Saldana & Company, Incorporated, is a large scale manufacturer of garments which is located at Pasig City. The company is composed of 14 primaries which are contractors owned by the company. At the group's study area or plant site, there are only 2 primaries present. These are BEZ Quality Garments and Letty Calvelo Enterprise which are the company's major producers of high fashion intimate apparel. The major product lines of the company include high fashion intimate apparel, ladies foundation garment, and babywear. High fashion intimate apparel covers 39% of the company's market sales and is the most common source of problems. For these reasons, the group decided to focus on this major product line. The major problem seen by the group in this company is that the management is very reactive in its planning and decision making. As problematic situations occur, the company tends only to adjust tho these problems and does not plant for long range benefits and problem prevention. AS a consequence, unnecessary and unexplained costs are incurred/ Thus the group analyzed the company's present operations management and production in order to resolve this problem. This was done by critically examining their demand management, pattern of workflow, operations planning activities, policies and controls that monitor levels of inventory and suggesting alternatives that the company might consider. At anytime of the year, the company knows its production requirement and demand (6) months ahead of time. It also applies a qualitative forecasting method which is not used. Knowing that the company has data for demand six months ahead of time, it still uses the actual demand rather than the forecast in its long term capacity planning. Therefore, the group recommended that they revise their present forecasting method and apply focus forecasting with an annual increase of 40% in their sales and use this to protect long term demand for capacity planning purposes. The suggested percentage is in line with the company's intended annual sales increase. Moreover, the group also suggested methods apt for long range capacity planning which are beneficial for each primary, BEZ Quality Garments and Letty Calvelo Enterprise. In addition to long range planning, the group suggested five (5) plans for aggregate planning and explained the advantages and disadvantages of each. These plans are Chase strategy, constant low workforce and subcontracting, constant workforce and varying inventory levels, constant workforce and overtime, and constant low workforce and overtime. The plan with the least cost that the group arrived at is subcontracting with a total cost P1,451,531.4.0 followed by maintaining constant low workforce with varying inventory with a total cost of P1,462,500 due to disadvantages of choosing plan 2 and plan 3. Choosing plan 2 will incur additional costs die to lack of quality control while plan 3 will incur cost due to the addition of a warehouse for each primary. Moreover, the group suggested the use of a product tree and an Materials Requirement Planning form which can be of use to the company. The company presently considers holding costs as negligible. The group recommended the consideration of holding costs for planning purposes because they are essential for costing and aggregate plans.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Saldana and Company Incorporated; Clothing trade; Production engineering